Post-operative Analgesia in Opioid Dependent Patients: Comparison of Intravenous Morphine and Sublingual Buprenorphine - Alizadeh, Shaabanali (Addict Health, 2015)
BACKGROUND: Acute and chronic pain is prevalent in patients with opioid dependence. Lack of knowledge concerning the complex relationship between pain, opioid use, and withdrawal syndrome can account for the barriers encountered for pain management. This study was designed to evaluate the efficacy of sublingual (SL) buprenorphine for post-operative analgesia, compared with intravenous (IV) morphine. METHODS: A total of 68 patients, aged 20-60 years were randomly selected from whom had been underwent laparotomy due to acute abdomen in a University Teaching Hospital in Arak, Iran, and were also opioid (opium or heroin) abuser according to their history. After end of the surgery and patients’ arousal, the patients were evaluated for abdominal pain and withdrawal syndrome by visual analog scale (VAS) and clinical opioid withdrawal score (COWS), respectively 1, 6, and 24 h after the surgery. They received either morphine 5 mg IV or buprenorphine 2 mg SL, 1 h after end of the surgery, and then every 6 h for 24 h. FINDINGS: VAS was 4.47 ± 0.73 and 2.67 ± 0.53 at h 6 and 24 in buprenorphine group, respectively. The corresponding score was 5.88 ± 0.69 and 4.59 ± 0.74 in morphine group. At the same time, patients in buprenorphine experienced less severe withdrawal syndrome. CONCLUSION: The present study confirmed the efficacy of SL buprenorphine as a non-invasive, but effective method for management of post-operative pain in opioid dependent patients. Result of this study showed that physicians can rely on SL buprenorphine for post-operative analgesia.